Stigma size as a target for wheat hybrid breeding: phenotyping germplasm diversity and mapping candidates underlying its genetic control - Knight, Christopher J. (2024)
Modifying bread wheat (Triticum aestivum) floral characteristics will be crucial to improve the efficiency of hybrid seed production. A larger and more-plumose stigma, on the female parent, is predicted to improve pollen capture potential and increase the chance of successful cross-fertilisation. A low-tech and potentially scalable method to phenotype carpel size was developed on a small panel of sterile lines, with an automated image annotation software package trained to automatically detect Pollen Capture Area (PCA) from the carpel images. The method proved to be accurate and was applied to different populations of diverse material that included: landraces, wild relative introgressions and synthetic hexaploids. Significant genotypic variation was observed for Stigma length (SL) and PCA. When studies were repeated over multiple years SL and PCA were consistent for individual lines, with a high calculated heritability for each trait. Using the phenotypic data, Genome-Wide Association Study (GWAS) was exploited to detect significant loci associated with each trait. Each genomic region was mined for potential candidate genes utilising expression data, gene ontology and ortholog information. Subsequently, preliminary GWAS results, and an analysis of literature was used to inform the selection of target genes for CRISPR-Cas9 mediated genetic analysis. Utilisation of this protocol and selecting for SL in breeding programs is discussed, with areas for future research identified.